The Role of Nahdatul Ulama (NU) in Ptomoting Islam Wasatiyyah (Moderate Islam) As A Counter- Narrative to Global Radicalism - Mirzon Daheri; Syafiq Amir; Rashid Rahman; Saiful Fallah (Journal of Noesantara Islamic Studies, 2025)
The rise of global radicalism in recent decades has posed significant challenges to the integrity and peace of the Muslim community. In response to this, Islamic organizations such as Nahdlatul Ulama (NU) have become pivotal in promoting Islam Wasatiyyah, or moderate Islam, as an antidote to extremism. NU’s unique position in Indonesia and its global influence present an opportunity to examine its role in counteracting radical ideologies. This study aims to explore the contributions of Nahdlatul Ulama in promoting Islam Wasatiyyah as a counter-narrative to the growing threat of global radicalism. It investigates how NU’s teachings and activities advocate for moderation, tolerance, and inclusivity in Islamic practices. This qualitative study employs a literature review and content analysis of key NU texts, official statements, and related theological works. Interviews with NU scholars and activists further enrich the understanding of NU’s strategies in promoting a moderate Islam. The findings suggest that NU’s emphasis on the middle path of Islam has provided a strong theological foundation against radical ideologies. Through its educational programs, interfaith dialogues, and advocacy for pluralism, NU has successfully advocated for Islam Wasatiyyah as a key component of peace-building efforts. Nahdlatul Ulama plays a significant role in fostering a moderate interpretation of Islam, thereby offering an effective counter-narrative to global radicalism. Its efforts are crucial in the global fight against extremism.